Implementasi Pendekatan Pembelajaran Berbasis Kearifan Lokal Dalam Meningkatkan Minat Belajar Siswa Di MTs Miftahus Sudur Campor Proppo - Nur Amaliyah; Nisrochah Hayati; Ria Kasanova (Universitas 45 Surabaya, 2023)
Implementation of a learning approach based on local wisdom at MTs Miftahus Sudur Campor Proppo increases students' interest in learning through connectedness to local culture, the relevance of learning, and strengthening cultural identity. The research method used is qualitative with interviews, observation, and documentation. The results showed high student enthusiasm, better involvement, and development of critical and creative abilities. Practical recommendations include teacher training, curriculum development, school-community partnerships, and the use of information technology. This research makes an important contribution to local wisdom-based education with in-depth understanding and practical guidance.